Effect of therapeutic exercise on joint range and strength in throwing athletes with dyskinesia. A systematic review - Álvarez‐Arangua, Sebastián; Arias Poblete, Leónidas; Espoz-Lazo, Sebastián; Silva Mella, Mauricio Alejandro; Parada Osses, Ben-yamin; Zamora Pinoleo, Jovina; Rubilar Henríquez, Cristian; Lizana Rodríguez, Catalina; Ríos-Riquelme, Mario; Farías‐Valenzuela, Claudio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The aim of this study was to determine the effect of using therapeutic exercise (TE) on changes in the range of motion (ROM) and muscle strength (MS) in throwing athletes with scapular dyskinesis (SD). A systematic review was carried out in databases (Pubmed, Scopus, WoS, ScienceDirect) over the last five years, searching for randomized clinical trials, cohort studies, meta-analyses and concept reviews that met the inclusion, exclusion, and methodological quality criteria. A total of six articles related to throwing athletes with scapular dyskinesia were included. Favorable results were found within the interventions that included TE, which obtained a significant effect on the variables of ROM and muscle strength in throwing athletes. In conclusion, therapeutic stretching exercises are the most favorable and effective tool compared to any other type of intervention, having an effect on the MS and ROM of throwing athletes, thus helping their competitive performance.